Adsorción óptima de ión plúmbico por pellets de microalgas tratadas con diferentes concentraciones de ácido clorhídrico. - Zarpán Ortiz, Rocío Del Pilar (2012)
The present investigation has been carried out with the purpose of determining the good concentration of HCl used in the treatment of micro algae for the adsorption of lead ion. The micro algae were obtained of the lagoons of treatment of residual waters of Covicorti-SEDALIB S. A., Trujillo, Peru. In the treatment were evaluated 3 concentrations of HCl : 0.125, 0.150 and 0.175 N. Like control group it was used micro algae that they were not treated previously with HCl. The process of adsorption was carried out carries out in an ideal solution of 5 ppm of lead ion at pH 5, with a temperature of 17ºC 3 ºC during 180 minutes, in a system of 4 packed columns with recirculation flow of 300 ml/min/cm2, it was observed that at 20 minutes of initiate the process the biggest percentage in the adsorption takes place for the three experimental groups, being achieved the biggest adsorption with the microalgae tried with HCl to the 0.15 N. The adsorption of mercury with the microalgae not treated is smaller than when the micro algae were treated with HCl.